Radiculomyelitic Rabies: Can MR Imaging Help? - Desai, Ravi V.; Jain, Vivek; Singh, Paramjeet; Singhi, Sunit; Radotra, Bishen Dass (American Journal of Neuroradiology, 2002)
Summary: Radiculomyelitic (silent) rabies and acute disseminated encephalomyelitis have similar clinical presentations but distinct management and prognostic implications. It is thus important to differentiate between the two antemortem. Because of their distinct pathologic abnormalities, MR imaging may be helpful in distinguishing between the two entities. We report a case in which MR imaging helped us to diagnose silent rabies antemortem, which was subsequently confirmed at autopsy.